QUALITY OF LIFE IN BREAST CANCER: THE BENEFITS OF PET OWNERSHIP AND PARTICIPATION IN LEISURE ACTIVITIES - Binotto, Monique; Daltoé, Tiago; Formolo, Fernanda; Spada, Patricia Kelly Wilmsen Dalla Santa (Mastology, 2017)
Objective: To evaluate the benefits in the perception of quality of life (QoL) of women with breast cancer related with pet ownership and experiencing leisure activities. Method: Cross-sectional study comparing QoL among patients, by applying the WHOQOL-Bref questionnaire. The participants were 272 women diagnosed with breast cancer. Results: The pet owners (n=162) had better average of QoL in perceptions of global QoL (72.45 vs. 67.16; p=0.01), and in environmental (67.52 vs. 64.23; p=0.04) and psychological domains (70.29 vs. 66.44; p=0.03) when compared to non-pet owners. Moreover, the patients who reported having leisure activities (n= 214) had better average in perceptions of global QoL (72.43 vs. 62.50; p<0.001), and physical health domain (63.28 vs. 50.92; p<0.001), environmental (68.22 vs. 58.67; p<0.001), psychological (71.01 vs. 60.34; p<0.001) and social relationships (74.73 vs. 65.09; p<0.001) when compared to those who do not have leisure activities. Conclusion: Women with breast cancer who are owners of pets and patients who perform leisure activities had better levels of QoL.